PENERAPAN TEKNIK DATA SCRAPING` UNTUK PENENTUAN KESESUAIAN LOKASI MINIMARKET BERDASARKAN ATURAN NIAGA DI JAWA BARAT - Harahap, Rina Muthia; Atmawidjaja, Rudie Rachmat; Kresnawati, Diah Kirana; Ridwan, Mohamad; Alamsyah, Denan Fajar (Jurnal Spasial, 2025)
Indonesian people are already familiar with retail MSMEs such as grocery stores/stalls/taverns. Currently, the choice of places to shop is increasingly diverse, including minimarkets. The results of research in Bogor City in 2022 show that 64% of minimarkets in Bogor City have a distance between minimarkets of less than 250 meters, which means they do not comply with commercial regulations in Bogor City. Other cities in West Java Province also have regulations regarding distance between minimarkets. Analysis of the distance between minimarkets can be carried out in a shorter time if data on the distribution of minimarkets has been obtained. Data on the distribution of hundreds of minimarkets can be mapped using data scraping techniques. The result is an excel file containing several pieces of information, including the minimarket address. Next, geocoding is carried out based on the address information. Then the distribution of minimarkets can be displayed via mapping software. The buffer method is used to analyze the distance between minimarkets according to the regulations applicable in a particular city. This research aims to produce a comparison of the suitability of minimarket locations based on the regulations that apply in the cities of West Java Province. The minimarkets referred to in this research are shops managed by business entities such as Alfamart, Alfamidi, Circle K, Indomaret, and Prima Freshmart. After going through the validation and distance analysis stages between minimarkets, the city of Bandung became the city with the highest number of minimarkets that did not comply with commercial regulations.